ALIH AKSARA DAN ALIH BAHASA TEKS INILAH KITAB YANG BERNAMA PARUKUNAN KARANGAN SYEH AL-ALIM MUFTI JAMALUDDIN BIN ALMARHUM AL-ALIM AL-FADHIL SYEH MUHAMMAD ARSYAD MUFTI BANJAR - Yanto, Andi Frizal; Nurizzati, Nurizzati; Zulfadhli, Zulfadhli (Jurnal Bahasa dan Sastra, 2018)
This paper aims to: (a) present the tansliteration of the teks Inilah Kitab yang Bernama Parukunan Karangan Syeh Al-Alim Mufti Jamaluddin bin Al-Alim Al-Fadhil Syeh Muhammad Arsyad Mufti Banjar, (b) presents the tanslation of the text Inilah Kitab yang Bernama Parukunan Karangan Syeh Al-Alim Mufti Jamaluddin bin Almarhum Al-Alim Al-Fadhil Syeh Muhammad Arsyad Mufti Banjar. This research is a philology research, by using descriptive method at data processing stage. The object of this research is the text Inilah Kitab yang Bernama Parukunan Karangan Syeh Al-Alim Mufti Jamaluddin Bin Almarhum Al-Alim Al-Fadhil Syeh Muhammad Arsyad Mufti Banjar. The method used in this study is adapted to the research stages. In this study the method used is the standard edition method. In the transfer phase, alpha script is used and at the transfer stage the language is used by the transfer method. The results of this study present the text tansliteration and translation of the teks Inilah Kitab yang Bernama Parukunan Karangan Syeh Al-Alim Mufti Jamaluddin bin Al-Alim Al-Fadhil Syeh Muhammad Arsyad Mufti Banjar which has been adapted to the Indonesian Spelling (EBI). Some of the Malay and Minangkabau vocabularies found in this text are retained.Keywords: transliteration, translation, text, philology